Updosing of nonsedating anti-histamines in recalcitrant chronic urticaria - Kiran Godse; Prachi Bhattar; Sharmila Patil; Nitin Nadkarni; Manjyot Gautam (Wolters Kluwer Medknow Publications, 2016)
Chronic urticaria (CU) is a persistent, debiliating condition that causes severe impairment on the quality of life (QoL) of patient by interrupting work productivity. Current guidelines recommend second-generation (nonsedating) anti-histamines for the treatment for all forms of urticaria. In patients who do not respond adequately to conventional doses of anti-histamines, it is recommended to increase the dose to up to four times to obtain control. But there are only few controlled studies that have assessed the efficacy and safety of nonsedating anti-histamines. Though sedating histamines are frequently used as an add-on therapy in severe cases, they have a negative impact on QoL by compromising sleep and performance. The use of other suggested therapeutic options (omalizumab, cyclosporine A, montelukast and dapsone) is also limited by paucity of data on their efficacy and adverse effect profile. Second-generation anti-histamines which are relatively safer require more proven data to support their judicious use to improve disease in patients with CU.